Dialog dan toleransi beragama di Kota Ambon: perspektif bekas pejuang Muslim Ambon - Farid, Muhammad (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
Subsequent to piece declaration of Malino II in 2002, it was claimed that Maluku may sustain its peace in a much longer time. A numerous attempts on establishing harmonious dialogues between religions and the combatant leaders have also been initiated. Yet, the conflicts could never stop to occur. At the present time, supported with the mission of pluralism and multiculturalism, the efforts to generate interreligious dialogs continue to commence, despite the strong confrontation from the Muslim ex-combatants who believed that these efforts might originate new conflicts. This writing is made based on the result of a phenomenological study on the daily life of Muslim ex-combatants in Ambon city. The findings has shown that the ex-combatants had proposed a typical and unique design of dialog. In fact, the tolerance was a sort of "multiple tolerance", which has a closer connotation to the concept of tolerance (tasamuh) in Islam - to the extent of displaying the act of receiving and forgiving without losing the sense of being cautious and conscious toward non-Muslim individuals. This embed mental state is set due to the past conflict which leaves a traumatic wound and excessive prejudices toward the non-Muslim community. However, in daily life, the Muslim ex-combatants still demonstrate an open and sincere conducts toward the non-Muslims-socialize and mingle with all. The Muslim ex-combatants have proven themselves to be an important role in taking part of the peace process in Maluku. The proposed dialogue and tolerance are designated for mutual tranquility and prosperity, with the basis of Islamic fundamental values.